Design of a Hybrid Monte Carlo Method for Line Radiation Transport Simulations in Magnetic Fusion. Issue 1 (16th April 2018) - Rosato, J.; Marandet, Y.; Reiter, D.; Stamm, R.
ABSTRACT: We report on a kinetic transport model for the Lyman line radiation in optically thick divertor plasma conditions encountered in exhaust systems in magnetic fusion devices. The model employs a modified kinetic Monte Carlo method designed to switch automatically between a true random walk and an effective one, which employs an ad hoc evaluation of the collision number in highly scattering regions. The method is suggested as a simple candidate for speeding up the kinetic transport codes currently involved in magnetic fusion research for ITER and DEMO divertor (power and particle exhaust system) design, without invoking the computationally more complex multiple scattering theories nor fully implementing the hybrid transport (discrete) diffusion Monte Carlo schemes (DDMC). Prototypical applications in one- and two-dimensional slab geometry are performed as an illustration.